Implementation of the Making Safeguarding Personal Approach to Strengths-based Adult Social Care: Systematic Review of Qualitative Research Evidence. (26th April 2022) - Ahuja, Latika; Price, Anna; Bramwell, Charlotte; Briscoe, Simon; Shaw, Liz; Nunns, Michael; O'Rourke, Gareth; Baron, Samantha; Anderson, Rob
Abstract: Since the Care Act (2014), there is fresh impetus for social workers to apply strengths-based approaches (SBAs) when working with adults. However, implementation challenges remain. This article presents our synthesis of seven studies that examined Making Safeguarding Personal (MSP). It was conducted as part of a systematic review that aimed to summarise research evidence on the implementation of different SBAs within adult social work in the UK. Qualitative studies were analysed using a framework synthesis approach. Four themes were identified: (1) MSP as an intervention: seen as initially demanding but with long-term advantages; (2) Culture and settings: required broad cultural changes; 'outward facing' and smaller/specialist councils tended to find this easier; (3) Individual characteristics: related to enhancing the knowledge, skills and confidence of practitioner and stakeholders in MSP; and service user willingness to engage; and (4) Embedding and sustaining MSP: depended on strong leadership and active engagement at all levels. We found a wide range of factors affecting the implementation of MSP. These may have broader relevance for other strengths-based models of social work practice. Abstract : There is a resurgence of policy and practice interest in promoting strengths-based approaches (SBAs) to adult social work. But there is no single or easily defined strengths-based intervention, and this presents challenges for implementing these approaches. Instead, social workers must integrate and adjust the principles of strengths-based working to achieve the best fit to their organisation's and community's circumstances. There is, therefore, a need to understand better how SBAs can be implemented more widely and consistently, and we synthesised evidence about the implementation of Making Safeguarding Personal (MSP) in this broader context. This systematic review has identified, summarised and synthesised qualitative research and evaluation evidence about the detailed factors enable or inhibit the implementation of MSP in adult social work within the UK. It also compares these findings with other key reports on implementing and embedding SBAs, and considers the wider applicability of these findings beyond the MSP initiative.